A single regulatory gene is sufficient to alter V ibrio aestuarianus pathogenicity in oysters - David Goudenège; Marie Agnès Travers; Astrid Lemire; Bruno Petton; Philippe Haffner; Yannick Labreuche; Delphine Tourbiez; Sophie Mangenot; Alexandra Calteau; Didier Mazel; Jean Louis Nicolas; Annick Jacq; et al. (Environmental Microbiology, 2015)
Summary Oyster diseases caused by pathogenic vibrios pose a major challenge to the sustainability of oyster farming. In F rance, since 2012 a disease affecting specifically adult oysters has been associated with the presence of V ibrio aestuarianus. Here, by combining genome comparison, phylogenetic analyses and high‐throughput infections of strains isolated before or during the recent outbreaks, we show that virulent strains cluster into two V . aestuarianus lineages independently of the sampling dates. The bacterial lethal dose was not different between strains isolated before or after 2012. Hence, the emergence of a new highly virulent clonal strain is unlikely. Each lineage comprises nearly identical strains, the majority of them being virulent, suggesting that within these phylogenetically coherent virulent lineages a few strains have lost their pathogenicity. Comparative genomics allowed the identification of a single frameshift in a non‐virulent strain. This mutation affects the varS gene that codes for a signal transduction histidine‐protein kinase. Genetic analyses confirmed that varS is necessary for infection of oysters and for a secreted metalloprotease expression. For the first time in a V ibrio species, we show here that VarS is a key factor of pathogenicity.

Mutation rate and genome reduction in endosymbiotic and free-living bacteria - Gabriel A. B. Marais; Alexandra Calteau; Olivier Tenaillon (Genetica, 2008)

Horizontal Transfer of Two Operons Coding for Hydrogenases Between Bacteria and Archaea - Alexandra Calteau; Manolo Gouy; Guy Perrière (Journal of Molecular Evolution, 2005)